2016
DOI: 10.1021/acs.biochem.6b00770
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Aminoglycoside Resistance Enzyme Regiospecificity by Mutation and Truncation

Abstract: Aminoglycosides (AGs) are broad-spectrum antibiotics famous for their antibacterial activity against Gram-positive and Gram-negative bacteria, as well as mycobacteria. In the United States, the most prescribed AGs, including amikacin (AMK), gentamicin (GEN), and tobramycin (TOB), are vital components of the treatment for resistant bacterial infections. Arbekacin (ABK), a semisynthetic AG, is widely used for the treatment of resistant Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus in Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…With sufficient selective pressure, the enzyme may adapt and elaborate upon this activity, resulting in new, potentially clinically important antibiotic resistance. This echoes the study of Holbrook and Garneau-Tsodikova on the expansion of the other domain of this bifunctional enzyme through mutation and truncation that leads to increased acetylation of arbekacin (31). As in their work, we observed that the mutated protein does not undergo changes that lead to a substantive difference in mechanism but simply exhibits weak-affinity alternative binding modes.…”
Section: Discussionsupporting
confidence: 89%
“…With sufficient selective pressure, the enzyme may adapt and elaborate upon this activity, resulting in new, potentially clinically important antibiotic resistance. This echoes the study of Holbrook and Garneau-Tsodikova on the expansion of the other domain of this bifunctional enzyme through mutation and truncation that leads to increased acetylation of arbekacin (31). As in their work, we observed that the mutated protein does not undergo changes that lead to a substantive difference in mechanism but simply exhibits weak-affinity alternative binding modes.…”
Section: Discussionsupporting
confidence: 89%
“…A small number of 6′- N -acetyltransferases with the AAC(6′)-I profile were found in Gram-positive bacteria [ 184 , 188 , 189 ]. The AAC(6′)-Ie enzyme is fused to the N -terminal end of the phosphotransferase APH(2″)-Ia, forming a bifunctional enzyme coded for by the aac(6′)-Ie-aph(2 ″ )-Ia fusion gene usually located within Tn 4001 -like transposons in Gram-positive bacteria [ 182 , 183 , 190 , 191 , 192 , 193 , 194 ]. These transposons have been found in plasmids as well as chromosomes of Gram-positive pathogens such as S. aureus , S. epidermidis , or Enterococcus faecalis [ 195 , 196 , 197 , 198 ].…”
Section: Amikacinmentioning
confidence: 99%
“…Other enzymatic approaches to generate N -acylated AGs using AMEs have been reported. Two AG acetyltransferases (AACs), including 3- N -AG acetyltransferase AAC(3) and AAC(6′)-APH(2″) with 6′- N -acetyltransferase and 2″- O -phosphotransferase activities, exhibited promiscuity towards a number of AGs, as well as diverse acyl-CoAs, resulting in the generation of novel mono- and hetero-di- N -acylated AGs [ 11 , 12 , 13 ]. However, the biological activities of most resulting analogs against resistant bacterial pathogens have not been reported.…”
Section: Introductionmentioning
confidence: 99%